Ancient rhetoric and the New Testament : the influence of elementary Greek composition - Parsons, Mikeal C. 1957- (Baylor University Press, 2018)
For the ancient Greeks and Romans, eloquence was essential to public life and identity, perpetuating class status and power. The three-tiered study of rhetoric was thus designed to produce sons worthy of and equipped for public service. Rhetorical competency enabled the elite to occupy their proper place in society. The oracular and literary techniques represented in Greco-Roman education proved to be equally central to the formation of the New Testament. Detailed comparisons of the sophisticated rhetorical conventions, as cataloged in the ancient rhetorical handbooks (e.g., Quintilian), reveal to what degree and frequency the New Testament was shaped by ancient rhetoric's invention, argument, and style. But Ancient Rhetoric and the New Testament breaks new ground. Instead of focusing on more advanced rhetorical lessons that elite students received in their school rooms, Michael Martin and Mikeal Parsons examine the influence of the progymnasmata--the preliminary compositional exercises that bridge the gap between grammar and rhetoric proper--and their influence on the New Testament. Martin and Parsons use Theon's (50-100 CE) compendium as a baseline to measure the way primary exercises shed light on the form and style of the New Testament's composition. Each chapter examines a specific rhetorical exercise and its unique hortatory or instructional function, and offers examples from ancient literature before exploring the use of these techniques in the New Testament.